Variation of granulometric and organic composition of the toposequence of soil in the microregion of Marabá-PA - Reis, Magda da Silva; Fernandes, Antonio Rodrigues; Grimaldi, Catherine; Sarrazin, Max; Grimaldi, Michel (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
The transformations in the Amazonian ecosystems, that occur from colonization process, it have been enough studied, however little have been considering the variations of the characteristics of the soil in the landscape. With the objective of evaluating the variation of the soil of a landscape of the Marabá (PA) region, a study was carried through involving the granulometric and organic composition of the soil. It tries to explain the variation of those characteristics in relationship the pedogenetics processes. The samples were removed of vertical profiles, in the top (Latosols), hillside (Cambisols) and low slope (Gleysols), in a topossequence with 300 m of extension, cultivated with Brachiaria brizantha. The analyses demonstrated the clay prevalence in Latosols and in Cambisols, and of sand in Gleysols, besides an accumulation of organic matter in surface. The increase in the silte values in depth is current of the presence of the alterites, that appears in variable depth according to the soil class. Differentiat pedogenetic intensity in function of the declivity and the form of the source, provoked variations the granulometric and organic constitution of the soil, throughout the profiles the topossequence, that contributed for characterization of a pedologic, composed system of Latosols, Cambisos and Gleysols, of high the low one source, respectively.